Construction of the expert system of geospatial analysis that employs scenarios for the automated data generation for a digital map - Drobaha, Gregory; Lisitsin, Vladimir; Safoshkina, Lyudmila; Morozov, Ihor; Poberezhnyi, Andrey (Eastern-European Journal of Enterprise Technologies, 2019)
This paper reports a study into the formalization of algorithms for solving problems, the generation of data for digital maps, as well as their implementation, through a set of simple operations that would be intuitively clear to a user who is not a specialist in the field of geoinformation technologies. The approach that has been proposed is based on the construction of typical scenarios for model execution. Such scenarios are edited and adapted to the use of alternative electronic terrain maps. The result of scenario operation is a set of data ‒ layers of a digital map based on the input parameters for the model and the problem-solving algorithms, compiled by an expert. That makes it possible to construct libraries of typical scenarios, to store them centralized, as well as provide a common access to the scenarios, and to exchange data among applications. The result of running a scenario is that the user is provided with a possibility, without writing a programming code, to perform complex operations on processing geographical data and to simulate various processes at an electronic terrain map. A geospatial analysis expert system has been developed, containing both the basic functions for geographical data processing and the high-level specialized models. A tree of decisions is built under a mode of visual construction of a problem-solving algorithm. We have implemented a conveyor of operations at which the data sources in an expert system derived when performing any operation are sent to the input of the next operation. The results of this research could be used in simulation models of military activities, the tasks on photogrammetry in designing the optimal routes to fly over a territory, and as an additional tool for analysis of terrain in geoinformation systems. There is a possibility to expand the functionality of an expert system and to add new types of operations. Thus, there is reason to assert that the process of automatic construction of data for digital maps requires specialized software and highly skilled users of geoinformation systems.